JCGG 2018
DOI: 10.24816/jcgg.2018.v9i1.03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of operating a falls prevention Community of Practice on falls in a residential aged care setting

Abstract: Background/Purpose: Falls are a leading adverse event in residential aged care (RAC) settings with prevention a global aim. The purpose of this study was to determine whether operating a falls prevention community of practice (CoP) delivering evidence-based prevention interventions could change the rate of falls and injurious falls in a RAC setting. Methods: A prospective quasi-experimental pre/post design was conducted. Participants were 13 RAC sites (779 beds) of a single RAC organization, with 20 multidisci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Hullick et al (2021) demonstrated reductions in hospital admissions and emergency department presentations and Hirdes et al (2020) showed reduced resident pain rates. Francis‐Coad, Haines, et al (2018) did not demonstrate a change in falls rates, however, their CoP was the only one to be evaluated at all four of Kirkpatrick's levels.…”
Section: Resultsmentioning
confidence: 93%
“…Hullick et al (2021) demonstrated reductions in hospital admissions and emergency department presentations and Hirdes et al (2020) showed reduced resident pain rates. Francis‐Coad, Haines, et al (2018) did not demonstrate a change in falls rates, however, their CoP was the only one to be evaluated at all four of Kirkpatrick's levels.…”
Section: Resultsmentioning
confidence: 93%